Enhancing autonomous learning in vocabulary learning strategies: a structural equation modeling analysis - Md Azmi, Nur Afiqah; Mustapha, Nik Hanan; Ishak, mohd sobhi; Khalil, 'Ammar (Research and Scientific Innovation Society (RSIS International), 2025)
This study explores the relationship between autonomous learning and vocabulary learning strategies (VLS), emphasising its importance in enhancing language acquisition. There is a scarcity of empirical data confirming the influence of autonomous learning on vocabulary learning strategies, particularly within the realm of learning Arabic as a foreign language (AFL). This study seeks to examine how autonomous learning fosters the development and application of effective vocabulary learning strategies among Arabic language learners. The quantitative data was gathered using a questionnaire employing a 5-point Likert scale that was administered to 144 diploma students majoring in Islamic Studies and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that learners who engage in autonomous learning are more likely to employ vocabulary learning strategies, indicating a significant relationship between autonomous learning and vocabulary learning strategies. This research underscores the critical role of autonomy in vocabulary learning, suggesting that educational frameworks should promote autonomous learning to optimize language outcomes. Future studies could investigate the impact of specific vocabulary learning strategies on learner autonomy